PENGARUH SELF COMPASSION ORANG TUA TERHADAP SOCIAL ANXIETY ANAK USIA DINI DI SURABAYA - Elsa Fatimatuz Zahro; Wulan Patria Saroinsong; Suharti; Muhammad Reza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social anxiety is a common emotional problem in early childhood that may hinder social development and interaction readiness. One parental factor assumed to reduce children’s social anxiety is parental self-compassion. This study aimed to examine the effect of parental self-compassion on social anxiety among early childhood children in Surabaya. A quantitative causal-comparative (ex post facto) design was employed. The sample consisted of 405 parents of children aged 3–6 years selected using stratified sampling. Data were collected using Likert-scale questionnaires measuring three dimensions of parental self-compassion (self-kindness, mindfulness, and common humanity) and children’s social anxiety. Data were analyzed using classical assumption tests and multiple linear regression with SPSS. The results indicated that parental self-compassion significantly affected children’s social anxiety simultaneously (F = 336.353; p < 0.05). Partially, all dimensions of self-compassion showed significant effects, with self-kindness as the strongest predictor. These findings suggest that higher parental self-compassion is associated with lower social anxiety in early childhood.